Family history of diabetes, hypertension, obesity and cardiovascular diseases in relation to self health-care - Jabbar, Javereeya A.; Al Masri, Alaa H.; Oweidat, Farah A.; Al Ahmad, Moustafa M.; Ali, Omnia B.; Oweidat, Zaid A.; Sreedharan, Jayadevan (International Journal Of Community Medicine And Public Health, 2023)
Background: To assess the prevalence of family history of DM, HT, CVD, and obesity and determine the methods of self-health care among participants with and without a FH of these disease(s). Self-testing methods such as screening for chronic metabolic diseases and lifestyle modifications were focused on. Methods: A cross-sectional study including 1000 participants above 18 years of age and a self-reported questionnaire was used to collect data. The association was assessed using the Chi-square test. Logistic regression was used to determine the degree of association. P≤0.05 was considered statistically significant. An informed consent was taken from all participants and ethics approval obtained from International Review of Boards Committee. Results: Results showed 44.8% with a FH of DM, 49.1% with hypertension, 21.9% with CVD and 17.3% with obesity. The OR showed that the likelihood of testing for FBG (OR=5, p<0.001 those with four FH compared to no FH), Cholesterol (OR=2.4, p<0.01 those with four FH compared to no FH), BP (OR=2.5, p<0.05 those with four FH compared to no FH), ECG (OR=2.1, p<0.01 those with four FH compared to no FH) and BMI (OR=7.7, p<0.001 those with four FH compared to no FH). Conclusions: Participants with more FH of disease were more likely to test for glucose, cholesterol, blood pressure, electrocardiograms and body mass index.